Mengungkap Stroke sebagai ‘Silent Killer’ pada Usia Produktif - Supriadin Supriadin; Imam Fajlurrahman; Nurul Jannah; Dian Apri Nelyanti; Sri Yuliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to identify and analyze various risk factors contributing to stroke among productive-age individuals and examine relevant preventive measures for this age group. This study employed a systematic literature review method, examining 70 scientific journals obtained through Google Scholar and PubMed databases. The search was conducted from December 1-3, 2025. Selected articles were evaluated The results indicate that the main risk factors for stroke among productive-age individuals include hypertension, diabetes mellitus, dyslipidemia, an unhealthy lifestyle (smoking, lack of exercise, alcohol consumption), stress, and family history. The majority of stroke cases among productive-age individuals are ischemic. Educational interventions such as counseling, stroke awareness communities, and youth empowerment have proven effective in increasing knowledge and encouraging healthy lifestyle changes. In conclusion, stroke among productive-age individuals is an urgent global health problem that requires urgent attention. A more intensive promotive and preventive approach is needed, including the active role of healthcare workers, especially nurses, as community educators. Early awareness and behavioral change are key to reducing the incidence of stroke among productive-age individuals. Keywords: Risk Factors, Stroke Patients, Silent Killer Stroke, Young Stroke